Is remittance cost a driver of trade misinvoicing? A case study of Vietnam - Quang Phu Tran (Journal of Economics and Development)
Purpose – This study aims to investigate the impact of remittance costs on trade-based money laundering (TBML) and provide insights into the relationship between remittance costs and TBML, particularly focusing on import over-invoicing and low-income trade partners. Design/methodology/approach – Utilizing an extended gravity model for TBML, bilateral data from Vietnam spanning 2011 to 2019 are analyzed to examine the correlation between remittance costs and TBML. Findings – The study reveals a positive association between remittance costs and TBML, highlighting the significance of reducing remittance costs to curb TBML. Research limitations/implications – The research is limited by the availability of data and focuses solely on Vietnam, implying potential variations in other contexts. Practical implications – Policymakers should consider reducing remittance costs as a strategy to combat TBML effectively. Social implications – Lowering remittance costs could contribute to the prevention of illicit financial activities, fostering economic stability and social development. Originality/value – This study provides novel insights into the relationship between remittance costs and TBML, offering valuable implications for policy formulation and anti-money laundering (ML) efforts.